Thoracic pain arising from cervical disorders - A case history - Judith Musiker (AOSIS, 1995)
A case study is presented where a cervical disorder is responsible for thoracic symptoms. Maitland's differentiation tests become essential in clarifying which area of the spine is the source of the symptoms. The results of the treatment suggest that intermittent cervical traction may be helpful in cases of this nature.